If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(6-4k)+6k=90
We move all terms to the left:
6(6-4k)+6k-(90)=0
We add all the numbers together, and all the variables
6(-4k+6)+6k-90=0
We add all the numbers together, and all the variables
6k+6(-4k+6)-90=0
We multiply parentheses
6k-24k+36-90=0
We add all the numbers together, and all the variables
-18k-54=0
We move all terms containing k to the left, all other terms to the right
-18k=54
k=54/-18
k=-3
| 1.2x+4.8=2.1-x | | 2(2a-7)=14 | | 3x+x+8=36 | | 50-2x+x=180 | | 4x/7=21-3x | | 0.05=y/5.984 | | 2q+8=21 | | 10x-100+5=10x-100 | | 2x+4/3=5x+3/4 | | 90+x=(3x+2) | | 1.4×x=84 | | 1.4×y=84 | | 0.05=5.984/y | | 9.6x−15.4=−4.4x−11.2 | | 7/2p-4=10 | | 0.238095=4/y | | x-3(3/7)=(2/3) | | 3x+1+2x+x=180 | | -9=x/6+x/7 | | F(4)=(1/3)x | | -4x-2(x+2)=16-(x-5) | | 3n=9/8 | | 0.238095=2/y | | 4x+6=57-5x | | 4.2=1/x | | 10x-2=358 | | 2/3(7/8+2y)-3/8=5/8 | | -26b+4=£0.9b-17 | | 6y-6y+9-1=0 | | 2(n-8)=2 | | 11x-22=-4(-1-6x) | | x+35=-5x+5 |